Organocatalytic enantioselective dearomatization of thiophenes by 1,10-conjugate addition of indole imine methides - Xingguang Li (Nature Portfolio, 2021)
Catalytic asymmetric dearomatization is a powerful tool for the rapid construction of diverse chiral cyclic molecules from cheap and easily available arenes. Here the authors show an organocatalytic enantioselective dearomatization of substituted thiophenes in the context of a rare remote asymmetric 1,10-conjugate addition.